Effect of sintering temperature on YBa2 Cu3 O7-δ prepared via modified decomposition method - Hapipi, Nurhidayah Mohd; Chen, Sookien; Shaari, Abdul Halim; Kechik, Mohd Mustafa Awang; Lim, Kean Pah; Shabdin, Muhammad Kashfi; Tan, Kar Ban; Lee, Oon Jew; Yap, Siew Hong; Alimi, Nur Humaira Yasmin Mohd; Hon, Xiao Tong (Penerbit Universiti Kebangsaan Malaysia, 2026)
In this study, YBa2 Cu3 O7-δ (Y-123) high-temperature superconductors were synthesised via a modified thermal decomposition method using metal acetate precursors, with the sintering temperature varied between 920 °C and 980 °C. Phase formation, microstructure, and superconducting properties were systematically studied. Thermogravimetric analysis (TGA/DTG) showed a multi-step decomposition process, with final oxide formation occurring at temperatures above 500 °C. X-ray diffraction (XRD) confirmed Y-123 as the dominant phase, accompanied by impurity phases such as Y2 BaCuO5 (Y-211) and BaCuO2. Scanning electron microscopy (SEM) showed significant grain growth from 0.85 µm to 1.36 µm as the sintering temperature increased from 920 °C to 980 °C, which enhanced the grain connectivity in the sample. Electrical resistivity measurements showed that all samples exhibited a consistent onset critical temperature (Tc-onset) of 93.1 K, while the zero-resistance temperature (T) increased from 75.1 K to 88.1 K as the sintering c-zero temperature increased from 920 °C to 960 °C. The improvement in superconducting performance is due to enhanced phase formation and increased grain connectivity. These findings indicate that optimisation of sintering temperatures is a key factor in improving the microstructure and superconducting properties of Y-123 samples.